The Effect Of Tax Knowledge And Tax Sanctions On Taxpayer Compliance With Service Quality As A Moderation Variable - Michel Valentin; Indah Rahmaputri (Journal of Management and Digital Business, 2025)
Purpose – This study aims to determine the effect of taxation and tax sanctions on taxpayer compliance with service quality as a moderating. Design/methodology/approach – This study uses qualitative data, the sample in this study were 150 individual taxpayers. This type of research uses purposive sampling, the data collection method uses a survey method, namely the author distributes questionnaires to respondents. The data analysis technique in this study used SEM PLS. Findings –Based on the results of the PLS version 3 test from the tests have been carried out, it shows that simultaneously and partially the tax knowledge variable has a posistive effect on taxpayer compliance. But service quality can moderate the effect of tax knowledge on taxpayer compliance, but service quality can moderate the effect of tax sanctions on taxpayer compliance Research limitations/implications – This study contributes to the literature by focusing on tax knowledge, tax sanctions and service quality needed for tax compliance to support the directorate general of taxpayer compliance movement.